Empirical description of human emotional life - VILIŪNAS, V.; PACEVIČIUS, J.; STONČIUS, V. (Psichologija, 1997)
In the present study 100 Ss were asked to register their type of activities chronologically, and the sign, intensity, and duration of emotions they experienced for one or two weeks. lndividual and group data were obtained concerning the duration of each emotion, the mead emotional level (algedonic average), the level of stability of their emotional life, the time devoted for each activity, and its average emotional attractiveness.